Indoor Screening of Bactericides against Kiwifruit Bacterial Canker - Lanquan, Liu; Dong, Wang; Lu, Liu; Guiyong, Qin; Qiong, Wu (Plant Diseases and Pests(植物病虫害研究：英文版), 2014)
[ Objective ] The paper was to screen the effective agents against kiwifruit bacterial canker in Wanzhou District of China. [ Method ] Ten kinds of com- mon commercial bactericides preliminarily screened were selected for indoor antibacterial test using paper plate method and plate streaking method, and six kinds of bactericides with good antibacterial effects were further screened for indoor toxicity test. [ Result] Chloramphenicoloethylicin had the best antibacterial effect, with EC50 of 36.34 rag/L; followed by Xintianxlucai No. 6 and embamycin, with EC50 of 83.21 and 92.34 mg/L, respectively. [ Conclusion] Cldoramphenicoloethylicin, Xintianxiucai No. 6 and embamycin screened in the test had good antibacterial effect against kiwifruit bacteriai canker in Wanzhou District, and chlorampheni- coleethylicin was the most effective agent. These three agents could be directly applied to control kiwifruit bacterial canker in production, while application time and climate conditions in fields should also be considered during the actual application process. It is suggested that three agents can be used alternatively in order to de- lay the resistance of plants.